Reflection on Basic View of Public Infrastructure for Infrastructure Asset Management in Indonesia - Hitapriya Suprayitno; Ria Asih Aryani Soemitro (Jurnal Manajemen Aset Infrastruktur & Fasilitas, 2019)
Infrastructure Asset Management is essential. In Indonesia nowadays, they, who enter and take a role in Infrastructure Asset Management is either an engineer or an economist. Both the engineer and the economist tend to see the infrastructure in infrastructure engineering way and the economy of infrastructure. A Basic View of Public Infrastructure for Infrastructure Asset Management in Indonesia needs to be formulated. The Public Infrastructure is viewed through several different following basic concepts: Infrastructure System, Infrastructure Function, Infrastructure Supply-Demand, Infrastructure Capacity, Infrastructure Operation, Infrastructure Deterioration, Infrastructure Maintenance, Infrastructure Life Cycle, Infrastructure Economics, Infrastructure Performance, Infrastructure Taxonomy.